Working a democratic constitution a history of the Indian experience - Austin, Granville (New Delhi : Oxford University Press, 2011)
This text tells a very human story of how the social, political and day-to-day lived realities of the Indian people has been reflected in, and in turn directed the course of, constitutional reforms in the country.
Originally published: 1999.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Democracy -- India; Constitutional history -- India; India -- Politics and government -- 1947-